A quantitative adaptation of the Wayne test for pyrazinamide resistance. (July 2016) - Meinzen, Christopher; Proaño, Alvaro; Gilman, Robert H.; Caviedes, Luz; Coronel, Jorge; Zimic, Mirko; Sheen, Patricia
Summary: Background: Pyrazinamide (PZA) is the most important drug against the latent stage of tuberculosis (TB) and is used in both first and second line treatment regimens. The continued increase in multi-drug resistant TB and the prevalence of PZA resistance makes the development of alternative assays for prompt identification of PZA resistance all the more important. Methods: We standardized and evaluated a quantitative variant of the Wayne assay (QW) for determining PZA resistance in Mycobacterium tuberculosis strains. This assay quantifies M. tuberculosis metabolism of PZA and production of pyrazinoic acid (POA) using visible spectrophotometry. We evaluated this method using PZA concentrations of 400 μg/ml and 800 μg/ml at incubation periods of 3, 5 and 7 days. M. tuberculosis strains from 68 sputum samples were also tested with the standard Wayne assay, Tetrazolium Microplate Assay (TEMA), Bactec 460TB and pncA sequencing. We compared QW and standard Wayne assay against a dichotomous reference classification using concordant Bactec 460TB and pncA sequencing. Secondarily, we determined the quantitative correlation between both QW values and TEMA's minimum inhibitory concentration (MIC) against Bactec 460TB percentage growth. Results: The standard Wayne showed sensitivity of 88% and specificity of 97.5%, giving a Youden Index (YI) of 0.855 against reference tests. The QW showed maximum YI of 0.934 on day 7 at 400 μg/ml PZA with 96% sensitivity and 97.4% specificity. Absorbance OD values for 400 μg/ml PZA were more accurate than 800 μg/ml PZA. Although QW showed high accuracy for PZA susceptibility, it did not correlate quantitatively with Bactec percentage growth. TEMA testing was unreliable and did not correlate with Bactec results. Conclusions: The proposed QW assay is an inexpensive method capable of providing standardization and automation of colorimetric PZA resistance testing, with better discriminatory than the standard Wayne assay.